Synthesis of Biobased Phloretin Analogues: An Access to Antioxidant and Anti-Tyrosinase Compounds for Cosmetic Applications - Laurène Minsat; Cédric Peyrot; Fanny Brunissen; Jean-Hugues Renault; Florent Allais (MDPI AG, 2021)
The current cosmetic and nutraceutical markets are characterized by a strong consumer demand for a return to natural products that are less harmful to both the consumers and the environment than current petrosourced products. Phloretin, a natural dihydrochalcone (DHC) found in apple, has been widely studied for many years and identified as a strong antioxidant and anti-tyrosinase ingredient for cosmetic formulations. Its low concentration in apples does not allow it to be obtained by direct extraction from biomass in large quantities to meet market volumes and prices. Moreover, its remarkable structure prevents its synthesis through a green process. To overcome these issues, the synthesis of phloretin analogs appears as an alternative to access valuable compounds that are potentially more active than phloretin itself. Under such considerations, 12 chalcones (CHs) and 12 dihydrochalcones (DHCs) were synthesized through a green Claisen-Schmidt condensation using bio-based reagents. In order to evaluate the potential of these molecules, radical scavenging DPPH and anti-tyrosinase tests have been conducted. Moreover, the UV filtering properties and the stability of these analogs towards UV-radiations have been evaluated. Some molecules showed competitive antioxidant and anti-tyrosinase activities regarding phloretin. Two compounds in particular showed EC50 lower than phloretin, one chalcone and one dihydrochalcone.